Inflammation in sickle cell disease: Differential and down-expressed plasma levels of annexin A1 protein - Torres, Lidiane S. [UNESP]; Okumura, Jéssika V. [UNESP]; Silva, Danilo G. H. [UNESP]; Mimura, Kallyne K. O. [UNESP]; Belini, Édis [UNESP]; Oliveira, Renan G. [UNESP]; Lobo, Clarisse L. C.; Oliani, Sonia M. [UNESP]; Bonini-Domingos, Claudia R. [UNESP] (Public Library of Science (PLoS), 2016)
Sickle cell disease (SCD) is an inherited hemolytic anemia whose pathophysiology is driven by polymerization of the hemoglobin S (Hb S), leading to hemolysis and vaso-occlusive events. Inflammation is a fundamental component in these processes and a continuous inflammatory stimulus can lead to tissue damages. Thus, pro-resolving pathways emerge in order to restore the homeostasis. For example there is the annexin A1 (ANXA1), an endogenous anti-inflammatory protein involved in reducing neutrophil-endothelial interactions, accelerating neutrophil apoptosis and stimulating macrophage efferocytosis. We investigated the expression of ANXA1 in plasma of SCD patients and its relation with anemic, hemolytic and inflammatory parameters of the disease. Three SCD genotypes were considered: the homozygous inheritance for Hb S (Hb SS) and the association between Hb S and the hemoglobin variants D-Punjab (Hb SD) and C (Hb SC). ANXA1 and proinflammatory cytokines were quantified by ELISA in plasma of SCD patients and control individuals without hemoglobinopathies. Hematological and biochemical parameters were analyzed by flow cytometry and spectrophotometer. The plasma levels of ANXA1 were about threefold lesser in SCD patients compared to the control group, and within the SCD genotypes the most elevated levels were found in Hb SS individuals (approximately three-fold higher). Proinflammatory cytokines were higher in SCD groups than in the control individuals. Anemic and hemolytic markers were higher in Hb SS and Hb SD genotypes compared to Hb SC patients. White blood cells and platelets count were higher in Hb SS genotype and were positively correlated to ANXA1 levels. We found that ANXA1 is down-regulated and differentially expressed within the SCD genotypes. Its expression seems to depend on the inflammatory, hemolytic and vaso-occlusive characteristics of the diseased. These data may lead to new biological targets for therapeutic intervention in SCD.